Diversidad genética de plantaciones de Musa acuminata y Musa balbisiana establecidas en el Ecuador utilizando RAPD’s. - Cruz Arevalo, Scott David (2017)
Ecuador has a diversity of Musaceas, which have been differentiated through morphological markers which present certain limitations as they are subject to environmental factors such as heliophania, rainfall, height above sea level, pests and new diseases. These do not allow the specificity of this technique. The objective of this work was to determine the genetic diversity of Musa acuminata and Musa balbisiana (bananas and plantains), with the use of RAPD’s, which are found in the germplasm bank of farm “La María” of the UTEQ. For which a protocol of DNA extraction was adjusted, its conservation is necessary to continue with research at the molecular level. The RAPD’s proved to be an accurate technique to differentiate species of genome A or B and degrees of genetic dissimilarity, where three groups were presented where the Orito being diploide AA was grouped with Manzano AAB and Cuarofilo ABB genetically similar and differentiated from the groups that AAB (Group A), AAA (Group B), genomes were bound. To find more differences between species, tests of physiological characters such as stomatal density in the abaxial and adaxial cuticle and their possible relationship with the resistance or susceptibility to Mycosphaerella fijiensis of certain cultivars were performed. The epidermis was removed and the number of stomata were counted in a Newbauer chamber with the help of the Optical Microscope with a 10X ocular increase and 40X objective, which were indirectly related since the resistance is observed more in the cultivars of M. balbisiana. The quantification tests of chlorophyll determined that bananas have higher amounts of total chlorophyll, this could be related to the form of consumption and the sweet taste of its fruits, highlighting the Guineo Seda.